Antimicrobial activity of three essential oils (cinnamon, manuka, and winter savory), and their synergic interaction, against Listeria monocytogenes. (26th June 2019) - Fratini, Filippo; Mancini, Simone; Turchi, Barbara; Sparagni, Daniele; Al‐Gwad, Alaa Abd; Najar, Basma; Pistelli, Luisa; Cerri, Domenico; Pedonese, Francesca
Abstract: Essential oils (EOs) are categorized as having antimicrobial, insecticidal, and antioxidant activities. For their antibacterial activity, EOs are widely studied as alternatives to antibiotics in human and veterinary medicines. The inhibitory and bactericidal activities of three EOs ( Cinnamomum zeylanicum, Leptospermum scoparium, and Satureja montana ) were determined against Listeria monocytogenes ATCC 7644. The chemical compositions of the EOs were determined through gas chromatography mass spectrometry (GC‐MS). Essential oils were tested alone or in binary and ternary combinations for both their inhibitory and their bactericidal activities. Binary and ternary mixtures were tested through a chequerboard assay, and thus fractional inhibitory and fractional bactericidal concentration indices were obtained in relation to the activity of each EO alone. The chemical composition of each EO had different percentages of the main classes of compounds. EOs showed high levels of monoterpenes (hydrocarbons and oxygenated), sesquiterpenes (hydrocarbons and oxygenated), and phenylpropanoids for winter savory, manuka, and cinnamon, respectively. Several synergistic activities against Listeria monocytogenes were demonstrated in binary and ternary mixtures of the EOs. Mixtures of the EOs tested showed potential for use as antibacterial products; moreover, because of the synergistic activities the mixtures could be used in lower quantities than individual EOs on their own. Abstract : Essential oils are often effective antimicrobial agents. Their combination amplifies their effects. This investigation sheds light on the synergistic activity of binary and ternary mixtures of essential oils against Listeria monocytogenes .